Analysis of strategies of the screening, diagnosis and prevention of cervical cancer: a systematic review (Revista Científica Integrada, 2023)
Objective: to analyze the best strategies used in screening, diagnosis and/or prevention of cervical cancer. Methods: systematic review, conducted in September 2023, using the guiding question “What are the best strategies used in screening, diagnosing and/or preventing cervical cancer?”. For the search, the databases and libraries Google Scholar, Biblioteca Virtual em Saúde, MEDLINE (via PubMed), EMBASE, Scopus and Web of Science were used. Studies were limited to clinical trials, longitudinal studies, implementation research and quasi-experimental studies, published between January 2018 and August 2023, in Portuguese, English or Spanish. After applying the specific search strategy in each database, 334 studies were identified, of which 11 were selected to compose the sample. Results: the main strategies identified were the association of HPV tests with cytology or colposcopy, the use of mHealth and artificial intelligence. Furthermore, emphasis was also given to the offer of kits for self-sampling to identify HPV and neoplastic lesions. Conclusion: the combination of screening tests seems to have been the best strategy found by clinicians and researchers around the world. Additionally, it is expected that diagnostic accuracy technologies will be implemented and adapted to different socioeconomic contexts. Further investigations are still needed that consider the cost-effectiveness and association of the tests surveyed.
Keywords: Uterine cervical neoplasms; Early detection of cancer; Technology